Information structure framework for ISMS planning and certification: Malaysian data - Shamala, Palaniappan; Chinniah, Muruga; Mohd Foozy, Cik Feresa; Chai, Wen Chuah; Mustapha, Aida; Ahmad, Rabiah (Institute of Advanced Engineering and Science, 2018)
Information security are becoming an important aspect of organizations. Organisations also are progressively conscious of its important in their business strategy. The awareness make organisations are currently applying for information security management system (ISMS) to effectively manage their information assets. Therefore, this research aims to provide an Information Structure Framework for ISMS planning and certification. Then Likert structured questionnaire was distributed and the findings have been analyzed using Rasch Measurement Model (RMM). The results from this study, managed to develop Information Structure Framework for ISMS. The proposed framework consists of information structure focuses on providing the information outline which is structured in a way, in which the components are put together to form a meaningful structure which can be navigated at any time. The framework contributes to the field of ISMS and certification area. The framework provides an awareness on knowing beforehand what to do and to what extent they are already conquering the information needed for getting clear direction and to develop ISMS.